Acid base status in swamp buffaloes (Bubalus Bubalis) fed rice straw and concentrate with addition of sodium - G Joseph (Indonesian Center for Animal Research and Development (ICARD), 2001)
An experiment was conducted to study the addition of NaHCO3 and Na2CO3 on acid-base status in swamp buffaloes, Three fistulated buffaloes were each introduced to dietary treatment control diett (50% rice straw + 50% concentrate), control + \0% NaHCO3 and diet control + 10% Na2CO3 in two times Latin Square Design. The diets contained 9,7% crude protein and 53% TDN to achieve maintenance requirements of the animals. Parameters measured include (l) Fed consumption, water consumption and urine volume. (2) pH in rumen fluid, saliva, bLood and urine, (3) natrium mineral content in rumen fluid, saliva, blood and urine. The results of the experiment showed higher pH in the rumen fluid, saliva, blood and urine of buffaloes due to supplementation of NaHCO3 and Na2CO3, Water consumption and urine volume was significanly increased as the effect of Na supplement. The acid-base status of buffaloes was apparently normal in all animals. Key words: Acid-base status, rice straw, concentrate, buffer, swamp buffaloes